2015
DOI: 10.1177/1470320314568520
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tacrolimus on podocyte injury inducted by angiotensin II

Abstract: This study investigated the protective effect of FK506 in podocytes and the correlation of TRPC6 with podocyte injury repair. Methods: MPC5 were cultured in vitro, parallel with the control group, an Ang II stimulation group, and an FK506 intervention group. The apoptosis rate with flow cytometry also detected TRPC6 mRNA and protein expression by RT-PCR and Western blot, and then observed the distribution of TRPC6 with indirect immunofluorescence labeling under confocal microscope. Results: The activities of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…To determine whether CsA and FK506 alleviate podocyte injury by reducing mitochondria dependent apoptosis, we preincubated PAN-treated podocytes with CsA or FK506 in vitro . Our results, consistent with previous findings142732, reported the anti-apoptotic effects of FK506 on podocytes. However, the effects of CsA on podocyte apoptosis are controversial.…”
Section: Discussionsupporting
confidence: 94%
“…To determine whether CsA and FK506 alleviate podocyte injury by reducing mitochondria dependent apoptosis, we preincubated PAN-treated podocytes with CsA or FK506 in vitro . Our results, consistent with previous findings142732, reported the anti-apoptotic effects of FK506 on podocytes. However, the effects of CsA on podocyte apoptosis are controversial.…”
Section: Discussionsupporting
confidence: 94%
“…9 Researchers suggested that TAC inhibited podocyte apoptosis through lowering TRPC6 expression. 21 Cabin1 is a natural selective inhibitor of CN, targeted inhibition of CN by Cabin1 prevented cardiomyocyte hypertrophy 22 and regulated the synaptic endocytosis of neurotransmitter vesicles. 23 Furthermore, researchers demonstrated that overexpression of Cabin1 in rheumatoid arthritis mice induced fibroblast-like synoviocytes apoptosis and alleviated arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…TAC effectively inhibits TRPC6 overexpression. Therefore, TAC reduces podocyte apoptosis and inhibits the damaging effects of angiotensin II on podocytes (23). Peng et al showed that TAC treatment reduces glomerular angiopoietin-like 4, glomerular immune deposits, and circulating IgG levels; decreases existing proteinuria; and promotes podocyte repair (24).…”
Section: Discussionmentioning
confidence: 99%